THE EFFECT OF EXERCISES ACCOMPANIED BY SOME PHYSIOTHERAPY METHODS (PROPOSED AND MANUFACTURED) IN IMPROVING THE RANGE OF MOTION OF THE KNEE JOINT AFFECTED BY THE COMPLETE CUTTING OF THE ANTERIOR CRUCIATE LIGAMENT - Ahmed Samir Dawood; Dr. Shymaa Ridha Ali Al -Araji (Galaxy International Interdisciplinary Research Journal, 2023)
The research aims to prepare rehabilitative exercises using suggested exercises that are easy to implement and use some of the various means manufactured and proposed to improve the range of motion of the knee joint for players with complete severing of the anterior cruciate ligament after surgical intervention, as well as using easy therapeutic methods, which are ultrasound and electrotherapy (Gal-Faradic - Tens) and infrared radiation, which is one of the natural means, so the researcher decided to research all of the mentioned methods together to identify the extent of their impact on the rehabilitation of the anterior cruciate ligament and the return of the injured athlete to his activity in the shortest possible time. The researcher used the experimental method using the (one group) method with two pre and post tests due to its suitability to the nature of the problem. The sample was chosen by the intentional method, which consisted of (3) players with complete severing of the anterior cruciate ligament after surgical intervention, based on a medical report from the specialist doctor. The main experiment (qualifying curriculum) was conducted for (12) weeks and (3) days per week, and after obtaining the data as a result of the tests and measurements, it was processed according to the statistical bag (SPSS) to analyze the results and included statistical tables that were scientifically discussed based on the presentation and analysis and based on To Arab and foreign sources, as well as previous studies.In the light of the findings, the researcher came out with the following conclusions: that the prepared approach has a positive effect in improving the range of motion of the knee joint after the surgical intervention of the anterior cruciate ligament, and that the use of exercises and the proposed and manufactured physiotherapy methods has a great effectiveness in improving the range of motion, also that the use of exercises and means The manufacturer did not leave any negative effects on the sample, but they obtained positive effects and rapid improvement.